FANTASY PLAY AND EMOTIONAL COMPETENCE OF PRE-SCHOOL CHILDREN - Subhash, P. D.; G. S, Anu; Ram, Sulekha (THE PRIMARY TEACHER, 2011)
The paper analyses the relation between fantasy play and emotional competence of pre-school children with a non-experimental research. The study concludes that the pre-school children give first preference to fantasy play during their nursery outdoor play. The study also proves that the children who spent more time in fantasy play possess high emotional competence.